Optimalisasi Coretax sebagai Instrumen Reformasi Birokrasi Fiskal: Perspektif Digital Era Governance - Kania Larissa; Esterlin, Stevani; Friskila, Octavia Alva; Frins, Viola Valencia (Al-Ijtima`i: International Journal of Government and Social Science, 2026)
The digitalization of tax administration has become a strategic agenda in modern fiscal governance reform. Indonesia addressed this challenge through the launch of the Core Tax Administration System (Coretax) in January 2025, integrating 21 tax administration modules into a single digital platform with an investment of IDR 1.2 trillion. Coretax is positioned as a primary instrument of fiscal bureaucratic reform within the Directorate General of Taxes. However, its implementation has encountered significant challenges, including technical disruptions, low user adoption, limited digital literacy, and stakeholder resistance. These issues reveal a gap between policy design and the practical realities of digital tax reform. This study aims to analyze the implementation of Coretax as an instrument of fiscal bureaucratic reform through the lens of Digital Era Governance (DEG), focusing on its three pillars: reintegration, needs-based holism, and digitization change. The study employs a systematic literature review with content analysis, drawing on national academic journals, tax regulations, and official reports from the Directorate General of Taxes. The analytical framework is grounded in Digital Era Governance, supported by New Public Management and Good Governance perspectives. The findings indicate that Coretax has achieved progress in system reintegration but continues to face deficits in service holism and comprehensive digital transformation. Optimizing Coretax requires strengthened change management, enhanced organizational capacity, and strategies to build public trust and fiscal legitimacy. This study contributes conceptually to the development of Digital Era Governance theory in the context of tax administration in developing countries while offering strategic recommendations for digital-based fiscal bureaucratic reform.